Psicoanálisis y budismo (2014)
ABSTRACT: Buddhism as a philosophical and religious worldview does not coincide with psychoanalysis as a clinical practice and research method. Nevertheless, the intervention techniques that Buddhist masters use with their pupils can be compared with interpretation and transference since paradox, silence, and contradiction are used, but with different purposes. This paper aims to show that relationship by keeping the differences.